2021
DOI: 10.1073/pnas.2016772118
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal protein A inhibits complement activation by interfering with IgG hexamer formation

Abstract: Immunoglobulin (Ig) G molecules are essential players in the human immune response against bacterial infections. An important effector of IgG-dependent immunity is the induction of complement activation, a reaction that triggers a variety of responses that help kill bacteria. Antibody-dependent complement activation is promoted by the organization of target-bound IgGs into hexamers that are held together via noncovalent Fc-Fc interactions. Here we show that staphylococcal protein A (SpA), an important virulenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 59 publications
4
47
0
1
Order By: Relevance
“…In line with recent results, IgG1 and IgG3 antibodies against WTA elicit effective C3b deposition on S. aureus (Fig. 1A) (34). Furthermore, IgG4 did not activate complement on S. aureus (Fig.…”
Section: Igg-mediated Complement Activation Does Not Always Correlatesupporting
confidence: 92%
“…In line with recent results, IgG1 and IgG3 antibodies against WTA elicit effective C3b deposition on S. aureus (Fig. 1A) (34). Furthermore, IgG4 did not activate complement on S. aureus (Fig.…”
Section: Igg-mediated Complement Activation Does Not Always Correlatesupporting
confidence: 92%
“…The recombinant production of the hexamerizing IgG1-RGY is reasonably straightforward and similar to the production of normal IgG1 antibodies, whereby the inclusion of the RGY mutations promotes extensive hexamerization in solution, as previously described. 14 , 20 , 57 The production of recombinant IgM, especially in its (IgM) 5 J “pentamer” format, is less straightforward as it requires the appropriate coexpression of the joining J chain and IgM subunits and the correct formation of all inter- and intrachain disulfide bridges ( Figure 1 A,B). Here, a pure aWTA (IgM) 5 J pentamer (with J-chain) was recombinantly expressed and purified by SEC.…”
Section: Resultsmentioning
confidence: 99%
“… 14 The therapeutic potential of these induced IgG hexamers is currently being investigated, especially for their role in complement activation. 17 20 …”
Section: Introductionmentioning
confidence: 99%
“…Although they do not impact the interaction with the antigen ( Fig. 2A ), they often prevent the recognition of the antibodies by other proteins and thus can block the antibody-mediated effector functions ( 67 , 68 ). First evidence for the presence of IBPs in mycoplasmas came in 1991, when Lauerman et al showed that two proteins in M. synoviae (∼80 and ∼90 kDa) are able to bind to the Fc part of chicken IgG ( 69 ).…”
Section: Mycoplasmas Directly Target the Host Antibodiesmentioning
confidence: 99%